Current Indications for Rib Fracture Fixation in Unstable Chest Wall Injuries - Vinall, Phil (MD Conference Express, 2014)
A flail chest injury occurs when a segment of the thoracic cage is separated from the rest of the chest wall. Such injuries are associated with severe pulmonary restriction; they generally require intubation and mechanical ventilation; and they are associated with high rates of morbidity and mortality. This article discusses flail chest injury data from the National Trauma Databank of North America, the use of open reduction and internal fixation, indications for chest wall repair, as well as the current need for additional trial data.